Phytochemical Screening and Larvicidal Activity of Millingtonia hortensis L.f. Flower Extract Against Aedes aegypti Linn. - Thongpoon, Chalermporn; Poolprasert, Pisit (Agriculture and Natural Resources, 2015)
The phytochemical composition and larvicidal efficacy of essential oils extracted from Millingtonia hortensis flowers against laboratory-reared Aedes aegypti mosquitoes were investigated. The essential oils of fresh M. hortensis flowers were extracted by maceration in petroleum ether at room temperature for 12 hr and provided yields of oils of about 0.02% (volume per weight) fresh weight. The aromatic volatile components of the essential oils were analyzed using gas chromatography coupled to mass spectrometry. Out of 36 compounds, 27 were identified and accounted for 85.84% of the chromatographable components. These included: solanesol (25.72%), trans–farnesol (19.71%), nerolidol (8.54%), n-hexadecanoic acid (6.77%), vanillin (6.20%), oleic acid (4.54%), linoleic acid (3.87%), L–linalool (3.37%), 1–octen–3–ol (1.67%), α–farnesene (1.22%) and methyl salicylate (1.03%). For the larvicidal bioassay, M. hortensis flower extract was added to the third to fourth Aedes aegiypti instars in various concentrations (control, 25, 50, 100, 250 and 500 parts per million). These larvae exhibited median lethal concentrations to kill 50% of the treated larvae in 24 hr of approximately 208.5 parts per million (ppm; Y = 20.089X + 4.935). Based on the mortality rate, the concentration at 500 ppm of extract showed the highest effectiveness in controlling the larvae with 98% mortality after exposure for 24 hr. This study suggests that this plant extract can be used for controlling mosquito larvae.